Systematic review of the development and effectiveness of digital health information interventions, compared with usual care, in supporting patient preparation for paediatric hospital care, and the impact on their health outcomes - Demblon, Marie-Claire; Bicknell, Colin; Aufegger, Lisa (Frontiers in Health Services, 2023)
Background and aim: Elective surgery can be overwhelming for children leading to preoperative anxiety, which is associated with adverse clinical and behavioural outcomes. Evidence shows that paediatric preparation digital health interventions (DHIs) can contribute to reduced preoperative anxiety and negative behavioural changes. However, this evidence does not consider their design and development in the context of behavioural science. This systematic review used the Theoretical Domains Framework (TDF) to evaluate the design and development of DHIs used to support children aged one to 14 years and their parents prepare for hospital procedures and determine any correlation to health outcomes. It also considered whether any behavioural frameworks and co-production were utilised in their design. Methods: A search of MEDLINE, EMBASE, PsycINFO and HMIC took place looking for original, empirical research using digital paediatric preparation technologies to reduce preoperative anxiety and behavioural changes. Limitations for the period (2000-2022), English language and age applied. Results: Seventeen studies were included, sixteen randomised control trials and one before and after evaluation study. The results suggest that paediatric preparation DHIs that score highly against the TDF: (1) are associated with improved health outcomes, (2) incorporate use of co-production and behavioural science in their design, (3) are interactive and (4) used at home in advance of the planned procedure. Conclusion: Paediatric preparation DHIs that are co-produced and designed in the context of behavioural science are associated with reduced preoperative anxiety and improved health outcomes and may be more cost-effective.